2013
DOI: 10.1007/s00340-013-5378-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimum spectral window for imaging of art with optical coherence tomography

Abstract: Optical Coherence Tomography (OCT) has been shown to have potential for important applications in the field of art conservation and archaeology due to its ability to image subsurface microstructures noninvasively. However, its depth of penetration in painted objects is limited due to the strong scattering properties of artists' paints. VIS-NIR (400 nm -2400 nm) reflectance spectra of a wide variety of paints made with historic artists' pigments have been measured. The best spectral window with which to use opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 27 publications
3
40
0
Order By: Relevance
“…5 that one of the pigment absorbs light between 600 and 1000 nm (band 1 and 2) and appears red in the RGB image, whereas the other pigment absorbs the visible (band 1) and infrared light beyond ∼1.3 μm (part of band 3) and then appears greenish in the RGB representation. This is consistent with the spectroscopic properties of the Prussian blue and Cerulean blue oil paintings [13]. An example of how three-band FF-OCM can be used for biological sample characterization is shown in Fig.…”
supporting
confidence: 83%
“…5 that one of the pigment absorbs light between 600 and 1000 nm (band 1 and 2) and appears red in the RGB image, whereas the other pigment absorbs the visible (band 1) and infrared light beyond ∼1.3 μm (part of band 3) and then appears greenish in the RGB representation. This is consistent with the spectroscopic properties of the Prussian blue and Cerulean blue oil paintings [13]. An example of how three-band FF-OCM can be used for biological sample characterization is shown in Fig.…”
supporting
confidence: 83%
“…The camera system had to operate over the complete spectral range identified as providing the most usable information: 1000 to ~2500 nm. The selected spectral range of 1000-2500 nm is based on the prior studies of the wavelength dependence of the transmission of the paint layer [1,6] and also a study that included the effect of the underdrawing material and the paint grounds [4]. This latter study examined only five spectral regions from 900 to 2500 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have summarized the results of experiments aimed at finding the 'optimal' spectral transmission window for pigments and paints used by artists [1,[4][5][6]. In general, such studies have found increasing transmission of light starting around ~700 nm and peaking at about ~2000 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The output of micro-SORS is compared with the results of the optical coherence tomography (OCT) technique that has emerged in substitution of invasive methods capable of recovering the cross-sectional structural information. OCT is a well established optical interferometric technique, particularly suited for probing semi-transparent materials in the medical field, mainly in ophthalmology, and recently also in cultural heritage to study stratified systems of paintings [5][6][7][8][9]. both mixed in acrylic media, here referred to as 'R' (red) and 'B' (blue).…”
Section: Introductionmentioning
confidence: 99%